Magnetic resonance neurography detects diabetic neuropathy early and with Proximal Predominance. Issue 6 (14th November 2015) - Pham, Mirko; Oikonomou, Dimitrios; Hornung, Benjamin; Weiler, Markus; Heiland, Sabine; Bäumer, Philipp; Kollmer, Jennifer; Nawroth, Peter P.; Bendszus, Martin
Abstract : Objective: The aim of this work was to localize and quantify alterations of nerve microstructure in diabetic polyneuropathy (DPN) by magnetic resonance (MR) neurography with large anatomical coverage. Methods: Patients (N = 25) with mild‐to‐moderate (Neuropathy‐Symptom‐Score [NSS]/Neuropathy Deficit Score [NDS] 3.8 ± 0.3/2.6 ± 0.5) and patients (n = 10) with severe DPN (6.2 ± 0.6/7.4 ± 0.5) were compared to patients (n = 15) with diabetes but no DPN and to age‐/sex‐matched nondiabetic controls (n = 25). All subjects underwent MR neurography with large spatial coverage and high resolution from spinal nerve to ankle level: four slabs per leg, each with 35 axial slices (T2‐ and proton‐density–weighted two dimensional turbo‐spin‐echo sequences; voxel size: 0.4 × 0.3 × 3.5 mm 3 ) and a three‐dimensional T2‐weighted sequence to cover spinal nerves and plexus. Nerve segmentation was performed on a total of 280 slices per subject. Nerve lesion voxels were determined independently from operator input by statistical classification against the nondiabetic cohort. At the site with highest lesion‐voxel burden, signal quantification was performed by calculating nerve proton spin density and T2 relaxation time. Results: Total burden of nerve lesion voxels was significantly increased in DPN ( p  = 0.003) with strong spatial predominance at thigh level, where average lesion voxel load was significantly higher in severe (57 ± 18.4; p  = 0.0022) and in mild‐to‐moderate DPN (35 ± 4.0; p  < 0.001) than in controls (18 ± 3.6). Signal quantification at the site of predominant lesion burden (thigh) revealed a significant increase of nerve proton spin density in severe (360 ± 22.9; p  = 0.043) and in mild‐to‐moderate DPN (365 ± 15.2; p  = 0.001) versus controls (288 ± 13.4), but not of T2 relaxation time ( p  = 0.49). Nerve proton spin density predicted severity of DPN with an odds ratio of 2.9 (95% confidence interval: 2.4–3.5; p  < 0.001) per 100 proton spins. Interpretation: In DPN, the predominant site of microstructural nerve alteration is at the thigh level with a strong proximal‐to‐distal gradient. Nerve proton spin density at the thigh level is a novel quantitative imaging biomarker of early DPN and increases with neuropathy severity. Ann Neurol 2015;78:939–948